A new species of genus Pseudaspidapion Wanat, 1990 (Coleoptera, Apionidae) from China - Miguel Alonso-Zarazaga; Miguel Alonso-Zarazaga; Zhiliang Wang; Runzhi Zhang (ZooKeys, 2011)
Pseudaspidapion botanicum sp. n. from China is described and figured. Its host plant is Grewia biloba G. Don var. parviflora (Bunge) Hand.-Mazz (Malvaceae: Grewioideae). The genus Harpapion Voss, 1966 is recorded as new for China and Vietnam and two comb. n. are proposed: Harpapion vietnamense (Korotyaev, 1985) (from Aspidapion) and H. coelebs (Korotyaev, 1987) (from Pseudaspidapion). A key to the known species of the genus Pseudaspidapion from China is presented.